PRAGMATIC PHENOMENA CONSTELLATION IN SPECIFIC CULTURE DIMENSION LANGUAGE STUDY - R Kunjana Rahardi (International Journal of Humanity Studies (IJHS), 2017)
The linguistic phenomena studied in pragmatics evolve over time. Among the pragmatic phenomena that can be mentioned here are: implicature, deixis, presupposition, entailment, language politeness, language impoliteness and language phatic. There are certainly other pragmatic phenomena outside the phenomena mentioned above. In the future, other new pragmatic phenomena are expected to arise, along with the better development of pragmatic studies. Among those pragmatic phenomena, the phenomenon of language impoliteness can be regarded as a new phenomenon. How the constellation of pragmatic phenomena in the language study with the specific culture perspective becomes the main issue discussed in this short article. The benefit obtained by understanding the constellation of this new pragmatic phenomenon is that the interpretation of the pragmatic intent or meaning of language impoliteness becomes increasingly sharp, profound and comprehensive because its association with other pragmatic phenomena is sometimes an inevitable fact.